A Novel Compound Heterozygous Mutation of HSD17B3 Gene Identified in a Patient With 46, XY Difference of Sexual Development. Issue 4 (17th May 2022) - Cocchetti, Carlotta; Baldinotti, Fulvia; Romani, Alessia; Ristori, Jiska; Mazzoli, Francesca; Vignozzi, Linda; Maggi, Mario; Fisher, Alessandra Daphne
Abstract: Introduction: Deficiency of the 17β-hydroxysteroid dehydrogenase type 3 (17 β-HSD3) is a rare autosomal recessive 46, XY Difference of sex development (DSD), resulting from pathogenetic variants in the HSD17B3 gene, which lead to absent or reduced ability to convert Δ4-androstenedione to testosterone in the fetal testes. Aim: This study aimed to present the clinical and genetic characteristics of an Italian patient receiving a diagnosis of 17 β-HSD3 deficiency in adulthood. The patient was raised as female and underwent early surgical interventions to correct virilized genitalia, leading to a significant sexual distress. Methods: At the time of the referral, a 20-gene Next Generation Sequencing custom-panel for DSD was performed on patient's genomic DNA. Results: A novel compound heterozygous mutation in HSD17B3 gene was identified, detecting a new variant (c.257_265delAGGCCATTG, p.) Conclusion: Novel genotype causing 17 β-HSD3 deficiency is presented. Furthermore, the patient's clinical history stresses the importance to actively involve these individuals in the decision-making process avoiding surgical intervention when the patient is not able to give fully informed consent.